Evaluation of Absolute Neutrophil Count in the Perioperative Setting of Sarcoma Resection - Gayathri Vijayakumar; Emma M. Steffer; Neil P. Buac; Matthew W. Colman; Steven Gitelis; Alan T. Blank (Advances in Orthopedics)
Introduction. Limb salvage surgery (LSS) is the preferred surgical treatment for bone sarcomas. Preoperatively, many patients receive chemotherapy and may develop neutropenia. No study has evaluated the effect of a low preoperative absolute neutrophil count (ANC) on postoperative outcomes following LSS. Methods. This was a retrospective review of 114 patients who underwent LSS for bone sarcoma from 2010 to 2020. Preoperative lab values were analyzed by logistic regression to identify the risk of developing surgical complications within 30 days, surgical site infection (SSI), and reoperation. Results. Three (2.6%) patients experienced a surgical complication within 30 days. Twelve (10.53%) patients experienced postoperative SSI. Twenty-nine (25.4%) required reoperation. Preoperative ANC was not a significant predictor of surgical complications within 30 days, SSI, or reoperation. The only independent predictor of worse overall survival was the presence of a pathologic fracture at the time of surgery. Conclusion. This is the first study to evaluate preoperative ANC on postoperative outcomes following LSS. We report no significant differences in surgical complications within 30 days, SSI, or reoperation with low preoperative ANC. Future studies with larger cohorts of neutropenic patients are needed to evaluate these outcomes, as our cohort had very few neutropenic patients due to selection bias.